Clinical efficacy of avatrombopag and recombinant human thrombopoietin in the treatment of chronic liver disease-associated severe thrombocytopenia: A real-world study - Wang, Yong-Shuai; Wang, Wei; Zhang, Sai; Zhang, Shen-Yu; Shen, Ai-Zong; Wang, Wei; Song, Hua-Chuan; Yao, Huan-Zhang; Song, Rui-Peng; Meng, Fan-Zheng; Li, Lei; Nashan, Bjoern; et al. (Frontiers in Pharmacology, 2022)
Purpose: To investigate the clinical efficacy of avatrombopag, an oral thrombopoietin receptor agonist, versus subcutaneous recombinant human thrombopoietin (rh-TPO) in the treatment of severe thrombocytopenia (TCP) associated with chronic liver disease (CLD). Methods: Clinical data of 250 patients with severe TCP associated with CLD were collected in a single hospital from January 2019 to January 2022. The main parameters measured were the therapeutic response rate, changes in platelets (PLTs), and adverse events. Propensity score matching (PSM) was used to avoid possible selection bias. Results: After PSM, a total of 154 patients were enrolled in the study: 77 in the avatrombopag group and 77 in the rh-TPO group. There was no statistically significant difference between the two groups in the effect of increasing the PLT count (Waldχ2 = 1.659, p = 0.198; Waldχ2 = 0.220, p = 0.639). In addition, no interaction between time and different medications was found (Waldχ2 = 0.540, p = 0.910; Waldχ2 = 1.273, p = 0.736). Interestingly, in the subgroup analysis, both before and after PSM, avatrombopag showed better clinical efficacy than rh-TPO in the treatment of TCP associated with CLD in Child‒Pugh Class A (88.89% vs. 63.41%, p =0.003; 81.33% vs. 61.76%, p = 0.043). Fewer patients reported dizziness in the avatrombopag group than in the rh-TPO group both before and after PSM (7.8% vs. 25.0%; 7.8% vs. 24.7%, p < 0.05). Conclusion: Both before and after PSM, avatrombopag showed better clinical efficacy than rh-TPO in the treatment of TCP associated with CLD in Child‒Pugh Class A and showed a lower incidence of dizziness in all patients.